Techno-Economic Feasibility Study of Net-metering Implementation in Rooftop Solar PV in Nepal - Pokhrel, Hardik (Journal of the Institute of Engineering, 2020)
While a plethora of new hydro generation capacity are, being constructed, other forms of energy like solar is still undeveloped in Nepal. As of May 2018, the total installed capacity of Nepal stands at 1060 MW, among which mere 0.68 MW (0.06%) is solar. Solar Rooftop holds potential for development of solar and recognizing this, AEPC had urban solar program with capital subsidy element. In addition, NEA announced Alternative Electricity Connected to Grid 2018, with Feed in Tariff of NRs 7.30 for 3 years paving way for net metering in solar rooftop. This paper discusses the techno-economic feasibility of solar net metering across domestic (both individual and high-rise apartments), commercial and institutional consumers with the FiT offered. The analysis is done in both scenarios; where there is no export to grid and where there is export to the grid possible. Sample data on LCOE and kWh demand for each segment are collected and system size and solar production is calculated using Helioscope. Along with this, rate of return and payback years is calculated with current benchmark pricing and industry wide assumptions. The results of these analyses show higher payback period (6-9 years) and unattractive return (<15%) in the BOOT model for rooftops. Even in segments like high-rise apartments and commercial consumers with minimum 500 kW size where returns are higher (>20%), limitations as rooftop space makes net metering an un-attractive proposition. This paper also provides current policy landscape and envisages addressing policy gaps, and learnings from international arena on success of net-metering including financial incentives and regulations provided to drive the net-metering growth in Nepal.